Regionalizm Południowego Pacyfiku – ewolucja i perspektywy rozwoju - Klecha-Tylec, Karolina (The South Pacific regionalism – evolution and perspectives for development, 2009)
Regionalism and regionalization are both becoming more and more important processes in the contemporary world economy. They result from globalization phenomena taking place in political, economic, and social spheres. Those processes are particularly significant in the peripheral regions, such as the South Pacific. The aim of the article is to present the institutionalization processes in the South Pacific, the evolution of economic and security regionalism, and to outline the economic theory of clubs for Pacific regionalis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 13-24